Activity of Ketepeng Cina (Cassia alata Linn) Leaves Extract to Cercospora personatum growth - Linda, Riza; Khotimah, Siti; Elfiyanti, Elfiyanti (Balai Riset dan Standardisasi Industri Pontianak, 2011)
Ketepeng cina (Cassia alata Linn.) was known as vegetal fungicides because it contains toxic materials to fungi. This study aimed to determined the concentration of ketepeng cina (Cassia alata Linn.) leaves extract that effective in inhibiting the growth of Cercospora personatum and to know the fungicide activity of ketepeng cina (Cassia alata Linn.) leaves extract on the growth of Cercospora personatum. This research was conducted through stage that were manufactured PDA media, isolation of Cercospora sp. and extracting ketepeng cina leaves. Fungicidal activity test was done using poisoning food method with 6 concentration level: 0%, 1%, 2%, 3%, 4%, and 5%. Experiment using Completely Randomized Design with 6 treatments and 3 replications, effect of variance between treatment were analyzed and followed by Duncans test. The results showed that the concentration of 3% effective in inhibiting the growth of Cercospora personatum. Fungicidal activity of leaves extract ketepeng cina against fungi Cercospora personatum categorized as strong in concentrations â¥ 3% and nature fungistatic.